High intramuscular adipose tissue content associated with prognosis and postoperative complications of cancers - Rongqiang Liu; Zhendong Qiu; Lilong Zhang; Wangbin Ma; Liuliu Zi; Kunpeng Wang; Tainrui Kuang; Kailiang Zhao; Weixing Wang (Wiley, 2023)
Abstract Sarcopenia has been considered an adverse prognostic factor in cancer patients. Intramuscular adipose tissue content, as a new marker of sarcopenia, can effectively reflect skeletal muscle quality. The aim of this study was performed to evaluate the association between high intramuscular adipose tissue content (IMAC) and survival outcomes and postoperative complications in cancer patients. Specific databases, including the Web of Science, Embase and Web of Science, were systematically searched to identify relevant articles evaluating the prognostic value of IMAC in cancer patients. Hazard ratios (HRs) or odds ratios (ORs) with 95% confidence intervals (CIs) were utilized for comprehensive analysis. All data analyses were performed using STATA 12.0 software. A total of 25 studies from 24 articles including 5663 patients were enrolled in the study. Meta‐analysis showed that high IMAC was associated with unfavourable overall survival (OS) (HR: 2.21, 95% CI: 1.70-2.86, P < 0.001), relapse‐free survival (RFS) (HR: 1.51, 95% CI: 1.30-1.75, P < 0.001) and disease‐specific survival (DSS) (HR: 1.64, 95% CI: 1.19-2.28, P = 0.003). Subgroup analysis revealed that high IMAC remained an adverse prognostic factor when stratified by different country, treatment methods, cancer type or analysis type. High IMAC had better predictive value for gallbladder carcinoma (GBC) (HR: 3.50, 95% CI: 1.98-6.17, P < 0.001), hepatocellular carcinoma (HCC) (HR: 1.84, 95% CI: 1.45-2.33, P < 0.001), pancreatic cancer (PC) (HR: 2.11, 95% CI: 1.67-2.66, P < 0.001) and colorectal cancer (CRC) (HR: 2.54, 95% CI: 1.27-5.10, P = 0.009). High IMAC was also identified as a significant risk factor for postoperative complications (OR: 2.05, 95% CI: 1.22-3.46, P = 0.007). High IMAC was associated with an adverse prognosis and an increased risk of postoperative complications in cancer patients. IMAC may be a good indicator of sarcopenia.